1965
DOI: 10.1071/ea9650404
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between fish meal and two Queensland meat and bone meals in bacon pig production

Abstract: Fish meal, containing 64 per cent crude protein, was fed at a level of 10 per cent, as a protein supplement, in rations based on grain sorghum. Food conversion and daily gain of pigs fed this diet, from shortly after weaning to bacon weight, was superior to that obtained on diets containing either 14 per cent of a 65 per cent or 16 per cent of a 49 per cent crude protein meat and bone meal. Superior performance was also obtained when this diet was compared with two mixtures of the lower protein meat and bone a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1967
1967
1984
1984

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…However, the linear improvement in growth rate was not examined for levels of herring meal in excess of 7 percent of the diet. In both the present trial and that of Todd and Daniels (1965) growth rates were improved by increasing the proportion of fish meal in the diet beyond 7 percent. Similarly Jones, Hepburn, Cadenhead, and Boyne (1962) found that growth performance between 35 and 100 lb live weight improved as the level of dietary fish meal was raised from 7.4 to 15.7 percent.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…However, the linear improvement in growth rate was not examined for levels of herring meal in excess of 7 percent of the diet. In both the present trial and that of Todd and Daniels (1965) growth rates were improved by increasing the proportion of fish meal in the diet beyond 7 percent. Similarly Jones, Hepburn, Cadenhead, and Boyne (1962) found that growth performance between 35 and 100 lb live weight improved as the level of dietary fish meal was raised from 7.4 to 15.7 percent.…”
Section: Discussionmentioning
confidence: 65%
“…A trend toward increased leanness with corresponding increases in the level of fish meal was noted by Todd and Daniels (1965), while in a larger trial Jones et at. (1962) obtained a significant response in carcass leanness to increasing the level of dietary fish meal from 7.4 to 15.7 percent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation